FACING CLIMATE CHANGE CHALLENGES: ADAPTATION AND MITIGATION POLICIES FOR A BETTER FUTURE - Loso Judijanto; I Wayan Gede Suacana; Eksa Rusdiyana (Adisam Publisher, 2024)
Climate change is a global problem and has become an urgent issue in this modern era. In recent decades, we have witnessed the serious impacts of climate change, such as rising global temperatures, increasing intensity of extreme weather, and decreasing environmental quality. All of this poses a big challenge for the sustainability of our environment. The challenges faced by the environment due to climate change are very complex and require serious attention. To effectively adapt and manage these diverse difficulties, Indonesia and the rest of the world must take proactive, preemptive measures. Climate change poses a significant problem that necessitates taking concrete steps to mitigate greenhouse gas emissions and adapt to current and future effects. By taking small steps to lower greenhouse gas emissions, such as limiting the use of motorized vehicles, beginning to use public transportation, conserving water and electricity, cutting back on the use of plastic waste, and planting trees in the surrounding area, the community can contribute to mitigation. This study conducted an exploratory evaluation of the literature using a qualitative descriptive approach. This research discusses adaptation in the context of climate change, preventive and responsive adaptation, mitigation in the context of climate change, and general mitigation policies such as reducing greenhouse gas emissions and developing renewable energy.